INFLUENCE OF REPRODUCTIVE HEALTH EDUCATION PROGRAMMES AND SERVICES ON SEXUAL BEHAVIOUR AMONG IN-SCHOOL ADOLESCENTS IN DELTA STATE, NIGERIA (2012)
Reproductive Health Education Programmes and Services (RHPS) have been developed to help adolescents acquire knowledge and skills to express their sexuality in life enhancing ways. It is however, noted that the monitoring and evaluation of RHPS have not been done by Delta state personnel to ascertain its effectiveness in curbing at-risk sexual behaviour of in-school adolescents in the State. Studies revealed that 80% of patients with abortion complicated issues are adolescents. Therefore, ignoring the reproductive and sexual health needs of adolescents will have dire consequences. The at-risk sexual health problems among in-school adolescents in Delta State can no longer be ignored due to its enormous consequences that affect not only the adolescents but families, communities and the nation at large. This has led to the increasing demand for expanded programming on RHPS. This study, therefore, evaluated Reproductive Health Education Programmes and Services and their impacts on Sexual behaviour among in- school adolescents in Delta State, Nigeria. The study adopted ex-post facto research design. The multi-stage, cluster random and purposive sampling technique were used to select 1939 respondents (1,515 students; 346 teachers; and 78 Health care providers) from 26 public secondary schools in Delta State. Three questionnaires: Questionnaire for Health Care Providers RHPS-HCP (r-0.74), Questionnaire for Students RHPS-STD (r-0.84), and Questionnaire for Teachers RHPS-TCP (r-0.81) were used. These were complemented with two sessions of FGD held with students. Five research questions were answered and nine hypotheses tested at 0.05 level of significance. Data were analyzed using percentages; t-test and multiple regressions. The qualitative data were content analysed. Reproductive Health Educational Programmes (RHEP) (F (4, 1510) =7.921; p<.05), Reproductive Health Services (RHS) (F (3, 1511) =15.221; p<0.5) and Youth-Friendly Health Services Environment (F (3, 1511) =35.299; p<0.5) had significant influence on in-school adolescents sexual behaviour. The relative contribution of RHEP was ranked as follows: family life education (β= 0.145), peer education (β= 0.066); the relative contribution of RHES was ranked as follows: contraceptive counselling (β=0.137), and HIV/STIs counselling (β= 0.179). Teachers did not observe significant positive changes in students’ sexual behaviour and also Reproductive Health Knowledge of in-school adolescents was not significant. Focus Group Discussions revealed that students agreed to delay sexual initiation and avoid abortion. Peer education was ranked as the most influential on the sexual behaviour of in-school adolescents followed by Sexuality education, Family life education and HIV/AIDs education. The study provided data base evidence that ongoing RHEP was curbing at-risk in-school adolescents’ sexual behaviour. Reproductive Health Education Programmes and Services (RHPS) influence adolescents’ sexual behaviour. Unfortunately, human and material resources, funds and poor Youth-friendly Services Environments constitute obstacles to meeting the sexual needs of in-school adolescents in Delta State of Nigeria. Hence, Delta State Government should allocate more funds, embark on periodic assessment of the programme, and the youth should be encouraged to get involved in the programmes.